HIV antiretroviral preexposure prophylaxis - Richard Tjan (Faculty of Medicine, Universitas Trisakti, 2013)
According to 3 field trials conducted in Africa, one among African women and two amongheterosexual couples, antiretroviral preexposure prophylaxis for prevention of HIV-1 has beenshown to be effective.(1-3) In preexposure prophylaxis, persons without HIV infection are givenan oral drug before they have sexual contact with HIV-infected partners.(4) The drug in questionis tenofovir disoproxil fumarate (TDF), a prodrug of tenofovir.(1) On the basis of the 3 field trials,the Antiviral Drugs Advisory Committee of the Food and Drug Administration has recommendeda combination of antiretroviral drugs (tenofovir/emtricitabine) for preexposure prophylaxis ofHIV.(5)TDF is currently indicated for the treatment of HIV in adults over 18 years of age orhepatitis B virus (HBV) infection in adults, or both. The drug is called a nucleotide reversetranscriptase inhibitor (NRTI), preventing the synthesis of viral copies by HIV reversetranscriptase or HBV DNA polymerase.(6) To retard the emergence of TDF resistance, the drugis usually given in combination with another antiviral, such as emtricitabine (FTC). Nucleic acidtesting for HIV virus when starting preexposure prophylaxis, may reduce the risk of resistance,but it is at present not an option in developing countries because of its high costs. Rare butpotentially serious adverse reactions to TDF are lactic acidosis and toxic effects on the liver andkidneys.(6) Because administration of TDF to healthy noninfected persons implies using the drugfor a prolonged period of many years, the long-term safety of TDF and the TDF-FTC combinationhas to be clearly established.(4)There is also a real possibility that preexposure prophylaxis may lead to relaxation of thecustomary precautions on the part of the sexual partners, such as engaging in increased riskysexual behavior or abandoning the use of conventional prophylactic measures (e.g. condoms). (4)This matter should be a problem for health educators.From a practical point of view, because of the potential of serious liver and kidney diseasecaused by TDF, the medical practitioner should prescribe preexposure prophylaxis only in highrisk cases, and not for prevention of HIV in otherwise healthy individuals, e.g. blood bankpersonnel or dental practitioners with a low risk of exposure to HIV, which are currently notindicated. Prescription should be done on an individual basis.Indeed, the old Hippocratic advice of not too readily prescribing any new modes of treatment,or in plain words - Wait and watch- still holds true. This is presumably one of the reasons for notblindly or overenthusiastically accepting HIV preexposure prophylaxis.